2023
DOI: 10.3389/fmicb.2023.1112638
|View full text |Cite
|
Sign up to set email alerts
|

A dark matter in sake brewing: Origin of microbes producing a Kimoto-style fermentation starter

Abstract: IntroductionIn Kimoto-style fermentation, a fermentation starter is produced before the primary brewing process to stabilize fermentation. Nitrate-reducing bacteria, mainly derived from brewing water, produce nitrite, and lactic acid bacteria such as Leuconostoc can proliferate because of their tolerance toward low temperature and their low nutritional requirements. Later, Lactobacillus becomes the dominant genus, leading to weakly acidic conditions that contribute to control yeasts and undesired bacterial con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…Our results showed that Loigolactobacillus , an anaerobic, homo-fermentative bacteria, became dominant in both environments. Similarly, in another study, Loigolactobacillus was identified as the dominant genus in nukadoko samples (Niwa, Chen et al ., 2023). The process through which adventitious bacteria are outcompeted by LAB at the later stages of fermentation is dependent on the types of LAB that dominate the microbiome (Ono et al ., 2014).…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Our results showed that Loigolactobacillus , an anaerobic, homo-fermentative bacteria, became dominant in both environments. Similarly, in another study, Loigolactobacillus was identified as the dominant genus in nukadoko samples (Niwa, Chen et al ., 2023). The process through which adventitious bacteria are outcompeted by LAB at the later stages of fermentation is dependent on the types of LAB that dominate the microbiome (Ono et al ., 2014).…”
Section: Discussionmentioning
confidence: 51%
“…Indeed, within the architectural environment in which the samples are placed, various microbes, known as the Microbiome of the Built Environment (MoBE), exist, which can influence the production of fermented foods (Gilbert and Stephens, 2018;Ito, 2023) . MoBE has been found to contaminate the fermentation starter in a sake brewery (Ito, Niwa, Kobayashi, et al , 2023) . Similarly to the effects of Lactobacillus dominance of the microbiome in other experiments involving nukadoko , the presence of Loigolactobacillus in our experiment may also provide stability to the fermentation process and prevent adventitious microbes from contaminating the nukadoko environment.…”
Section: Changes In Taxonomic Composition During Fermentation Of Nuka...mentioning
confidence: 99%
“…However, these analyses did not determine whether the same bacteria were transferred or shared. To precisely evaluate the sharing of the gut microbiota between humans and dogs, we conducted a shared ASV analysis, which is an approach for inferring the sharing ratio of the microbiome at the ASV level between samples and has been used previously (31,40,41). While the sharing of ASVs was not detectable after two weeks of cohabitation, it was observed in the first and third months.…”
Section: Discussionmentioning
confidence: 99%
“…Shared ASVs analysis was performed based on a previous study 26,27 . We defined shared ASVs as ASVs shared by >1.0% of both samples in this study.…”
Section: Methodsmentioning
confidence: 99%